(3GdCLhHI GdRcjI Yf GdCdZGR GdSHcjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO abO hba GdYHO cGJH gPg GdGMQa abjQ QMeg QHg eMeO Hf Ydi Hf ShOhf GdMfai Ydi SDGd cJHg bGVi GdbVGg TjN GdGSdGe JGL GdOjf CHh fUQ GdSHci s
(3BNQgG (B:s
(3hef jYGfjg dG EKe Ydjg EPG QGYi GdbhGYO ajg ZjQ eaJhf Je GdLhGH HgPG Yf eSGFdg aGdMeO ddg MeOkG ZjQ eefhf Ke GdUdGI Ydi GdgGOi hYJQJg hUMHg eG CJi TGO HehRhf s
(3LhGH Ydi SDGd JGL GdOjf CHh fUQ GdSHcj Edi LdGd GdOjf Ndjd Hf CjHc GdUaOjs
Keywords: (3Gdabg GdMfajs